What drives European port traffic? The role of competition. (2018) - Fageda, Xavier; Gonzalez-Aregall, Marta
This article examines the determinants of traffic in European ports in 2010 by estimating a generalised linear model with a gamma distribution. We examine the influence of various economic and geographic attributes of the urban areas in which the ports are located, along with the influence of variables that identify the intensity of competition that the respective port authorities face. We include a range of explanatory factors of port traffic including the GDP of the urban area, location, the share of transhipment traffic, the share of dedicated terminals, the volume of traffic from neighbouring ports, the level of connectivity with other transportation modes and the port's model of governance. Our results suggest that variables outside of port manager control, like the economic size of the urban area or the amount of traffic of neighbouring ports, are key determinants of the traffic that a port is able to reach.